THE RE-AIM MODEL FROM THE PERSPECTIVE OF TELEPHONE-BASED EDUCATIONAL PROGRAMS ON DIABETES - Teixeira,Carla Regina de Souza (2019)
ABSTRACT Objective: to analyze the dimensions of the RE-AIM model from the perspective of telephone-based educational programs on diabetes, considering the experience of researchers from a public university in the state of São Paulo, Brazil. Method: this reflexive study presents an analysis of the dimensions of the RE-AIM model and the validity of its Brazilian version concerning the dimensions: reach, efficacy, adoption, implementation, and maintenance of results obtained by the study Telephone Support for the Follow-up of Diabetes Mellitus. Results: the analysis shows that the five dimensions provide information concerning factors that may affect the success of a program in clinical practice; that reaching the population remains a challenge; and that efforts should be made to advance on the efficacy and maintenance of educational interventions. Conclusion: this reflection, based on the experience of telephone-based educational interventions for diabetes, can contribute to advance Nursing science in terms of methodological guidance to support the development of interventions and programs at the various levels of health care.